FIXED-POINT OBSERVATION AND CHARACTERIZATION OF RADIOACTIVE CS IN SOIL COLLECTED AT KAWASAKI, JAPAN. Issue 13 (9th September 2022) - Saito, Rintaro; Inose, Satoshi; Koike, Yuya
Abstract: Radioactive Cs derived from the Fukushima Daiichi Nuclear Power Plant accident was detected in soils sampled at Kawasaki, Japan. Radioactive Cs adsorbed on soil is hard to be removed. Fixed-point observation of radioactive Cs concentration was performed on two observation sites of Meiji University. The soil samples were also analyzed for the distribution of radioactive Cs concentration and chemical form. 10 years after the accident, the activity concentration of radioactive Cs in soil samples at the Ikuta Campus of Meiji University ranged from 127 to 448 Bq kg −1 . The sequential extraction method results indicated that most radioactive Cs in the surface soil exists in a poorly soluble form.